Quasi-static and cyclic failure behavior of electric sheet material. (January 2016) - Bode, B.; Brueckner-Foit, A.; Zeismann, F.
Highlights: Tensile loading: ductile–brittle fracture; grain necking as ductile failure mode. Plastic deformation visible as grain rotation. Almost horizontal fatigue curves. Fatigue: mild notches with plastic deformation more detrimental than sharp notches. Failure behavior of punched specimens similar to specimens with polished edges. Abstract: The failure behavior of electric sheet material is investigated under quasi-static and under fatigue loading. Specimen were cut from plates, but also from punched rotor sheets. It was found that the S–N-curve is almost a horizontal line with the maximum stress at endurance limit just below the elastic limit in a tensile test. Cyclic failure was caused by shallow notches caused by plastic deformation in the manufacturing process or by angular holes formed by debonded AlN particles. Local plastic deformation was analyzed using high resolution orientation microscopy. No slip bands were found during cyclic loading; instead, there were some kind of wide-spread deformation bands in which cyclic plasticity was localized. These findings are related to the observed failure behavior.